Myopia in school-aged children and its relationship with screen time: an integrative review - Farias, Laiza Gallo (2024)
Myopia is becoming increasingly prevalent worldwide and can increase the risk of eye diseases such as glaucoma. Prolonged exposure to screens is a risk factor that has been associated with an increased risk of developing myopia in children. With the increasing use of electronic devices by children, it is important to better understand this relationship and evaluate screen use practices to prevent and treat myopia. There are few studies that address this topic in Brazil and worldwide. This study was an integrative analysis, carried out in six phases, according to the model outlined by Mendes, Silveira and Galvão. The systematic search/sampling was performed through an electronic search of the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Web of Science (Clarivate), Scientific Electronic Library Online (SCIELO), Scopus and Virtual Health Library (BVS) databases. Controlled descriptors from Medical Subject Headings (MeSH) and Health Sciences Descriptors (DeCS) were used to perform the bibliographic search in the databases, according to the following equation: “myopia” or “myopia” and “Criança” or “Child” and "Tempo de Exposição" or "Níveis Máximos Permitidos” or Threshold Limit Values". To determine the level of evidence of the selected articles, the classification proposed by the Agency for Healthcare Research and Quality (AHRQ) was adopted. The article selection process resulted in a total of 139 publications, of which 36 were excluded due to duplication, and 100 because they were not related to the theme of this review. Six articles were selected and the data were grouped into three categories, namely: 1- Mixed evidence on screen time and myopia; 2- Impact of screen time and outdoor activity on children with myopia; 3- Practical recommendations to mitigate the risk of myopia in children. This study found that some studies suggest a positive link, while others do not find a significant association, highlighting the need for more well-controlled research to better understand this relationship. Therefore, actions such as: limiting screen time, encouraging outdoor activities and adopting healthy visual habits may be effective strategies to mitigate the risk of developing myopia in children.